2015
DOI: 10.5535/arm.2015.39.1.74
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Post-Stroke Depression on Rehabilitation Outcome and the Impact of Caregiver Type as a Factor of Post-Stroke Depression

Abstract: ObjectiveTo evaluate the effect of post-stroke depression (PSD) on rehabilitation outcome and to investigate the risk factors of PSD, especially, the role of caregivers type (family or professional) in subacute stroke patients.MethodsTwo hundred twenty-six stroke patients were enrolled retrospectively. All the subjects' basic characteristics, Korean version of the Beck Depression Inventory (K-BDI), Korean version of the Modified Barthel Index (K-MBI), and the modified Rankin Scale (mRS) were recorded when the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 29 publications
1
41
2
Order By: Relevance
“…Regarding the important role of Left Pre-Frontal lobe in experiencing mood disorders, severe depression symptoms were more prevalent in stroke patients with left hemisphere lesion [44]. Furthermore, several open-label studies have suggested that left DLPFC cathodal and right DLPFC anodal tDCS may be an effective treatment configuration in more severely depressed subjects [45], as we employed in the present study for the third participant in the tDCS condition.…”
Section: Relation Between Tdcs and Ppmentioning
confidence: 90%
“…Regarding the important role of Left Pre-Frontal lobe in experiencing mood disorders, severe depression symptoms were more prevalent in stroke patients with left hemisphere lesion [44]. Furthermore, several open-label studies have suggested that left DLPFC cathodal and right DLPFC anodal tDCS may be an effective treatment configuration in more severely depressed subjects [45], as we employed in the present study for the third participant in the tDCS condition.…”
Section: Relation Between Tdcs and Ppmentioning
confidence: 90%
“…Furthermore, they usually prevent patients from returning to their jobs and have independent lives (35). As long as a person's cognitive system is involved with stressful events related to a trauma, his/her memory structure has a low performance (36), which decreases adherence and response to rehabilitation (37) as well as affects the person's quality of life and improvement of his/her performance (38). On the other hand, the better memory a person has, the more he/she follows a treatment (39).…”
Section: Discussionmentioning
confidence: 99%
“…There are vitamin D receptors in the hypothalamus, which may be important in neuroendocrine functioning [ 65 ]. Several studies identify an unfavorable influence of depression on functional outcomes after stroke [ 66 , 67 ], indicating the potential benefit of assessing and addressing nutritional inadequacies associated with depression in stroke survivors undergoing rehabilitation focused on functional recovery.…”
Section: Consequences Of Inadequate Nutrition In Chronic Strokementioning
confidence: 99%